NARASI PROSES PENGAMBILAN KEPUTUSAN IDENTITAS AGAMA ANAK DARI ORANG TUA BEDA AGAMA - Rahna Awal Permata Lades Rahna Awal Permata Lades; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study aims to understand the process of religious identity decision-making among children from interfaith families. This research employed a qualitative method with a narrative approach. The analysis was conducted using decision-making theory and interpersonal communication theory to examine how religious identity is formed and negotiated through everyday communication and interpersonal relationships. The findings show that the process of religious identity decision-making occurs gradually. The first stage begins with the identifying of identity-related problems caused by different religious experiences and uncertainty regarding religious identity. The second stage involves the exploration of religious identity through information seeking, religious experiences, and communication with family members and the surrounding social environment. The third stage is the consideration of consequences and relational risks related to the decision that will be taken. The fourth stage involves the communication and negotiation of religious identity decisions, where children begin to express their choices to certain individuals. The final stage is the establishment of religious identity, in which children either change, reaffirm, or consciously maintain their religious identity. This study reveals that religious identity decision-making is not an instant or purely individual process. Instead, it is shaped by interpersonal relationships, communication within the family, religious experiences, and the social environment surrounding the children.